Atypical intrinsic neural timescales in temporal lobe epilepsy. Issue 4 (1st March 2023) - Xie, Ke; Royer, Jessica; Lariviere, Sara; Rodriguez‐Cruces, Raul; de Wael, Reinder Vos; Park, Bo‐yong; Auer, Hans; Tavakol, Shahin; DeKraker, Jordan; Abdallah, Chifaou; Caciagli, Lorenzo; Bassett, Dani S.; et al.
Abstract: Objective: Temporal lobe epilepsy (TLE) is the most common pharmacoresistant epilepsy in adults. Here we profiled local neural function in TLE in vivo, building on prior evidence that has identified widespread structural alterations. Using resting‐state functional magnetic resonance imaging (rs‐fMRI), we mapped the whole‐brain intrinsic neural timescales (INT), which reflect temporal hierarchies of neural processing. Parallel analysis of structural and diffusion MRI data examined associations with TLE‐related structural compromise. Finally, we evaluated the clinical utility of INT. Methods: We studied 46 patients with TLE and 44 healthy controls from two independent sites, and mapped INT changes in patients relative to controls across hippocampal, subcortical, and neocortical regions. We examined region‐specific associations to structural alterations and explored the effects of age and epilepsy duration. Supervised machine learning assessed the utility of INT for identifying patients with TLE vs controls and left‐ vs right‐sided seizure onset. Results: Relative to controls, TLE showed marked INT reductions across multiple regions bilaterally, indexing faster changing resting activity, with strongest effects in the ipsilateral medial and lateral temporal regions, and bilateral sensorimotor cortices as well as thalamus and hippocampus. Findings were similar, albeit with reduced effect sizes, when correcting for structural alterations. INT reductions in TLE increased with advancing disease duration, yet findings differed from the aging effects seen in controls. INT‐derived classifiers discriminated patients vs controls (balanced accuracy, 5‐fold: 76% ± 2.65%; cross‐site, 72%–83%) and lateralized the focus in TLE (balanced accuracy, 5‐fold: 96% ± 2.10%; cross‐site, 95%–97%), with high accuracy and cross‐site generalizability. Findings were consistent across both acquisition sites and robust when controlling for motion and several methodological confounds. Significance: Our findings demonstrate atypical macroscale function in TLE in a topography that extends beyond mesiotemporal epicenters. INT measurements can assist in TLE diagnosis, seizure focus lateralization, and monitoring of disease progression, which emphasizes promising clinical utility.